Art Work : Women Artists and Democracy in Mid-Nineteenth-Century New York - Masten, April F. (Book collections on Project MUSE., 2008)
Between 1850 and 1880, thousands of women moved to New York City to study art and pursue careers as painters, designers, illustrators, and engravers. This book reconnects their accomplishments to the city's conspicuously democratic art institutions, its burgeoning illustrated press, and the prevailing aesthetic ideal known as the Unity of Art.